Objetivos de Desenvolvimento Sustentável para a educaç\~ao e a situaç\~ao brasileira: Breves notas para o debate público - Milko Matijascic (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This paper presents the content of the proposals for adapting all ten goals of SDG 4 for Brazil, in April and May 2018 and the levels of coverage and performance to be reached in 2030, when its validity ends. Next, the study presents indicators of the evolution of these goals until the most recent period and the challenges that are imposed, so that they are finally achieved, making the actions carried out in the context of the United Nations 2030 Agenda successful, whose period began in 2016.
Keywords: I20; I21; I24; 330; education in Brazil; sustainable development goals (SDGs); monitoring SDG indicators; adaptation of SDG 4 to Brazil